Potentiodynamic Study of Glucose Electro‐Oxidation at Bright Platinum Electrodes - Fernández Lorenzo de Mele, Mónica Alicia (1982)
The potentiodynamic electro‐oxidation of glucose on bright Pt in different electrolytes has been investigated through the application of combined potential/time perturbation programs. The E/I response in the 0.6 – 1.0V range (vs. SCE) depends on the perturbation conditions, the electrolyte composition, and the presence of CO2. The glucose electroadsorption process has been measured through potentiostatic current transients. The influence of anions in the electro‐oxidation reaction has also been studied. The interaction between electroadsorbed species and H‐adatoms, as well as the overall response of the electrochemical system suggests a reaction pattern that is more complex than those previously reported.